PSYCHOMOTOR AGITATION THERAPEUTIC GUIDELINES OF THE PSYCHIATRIC SECTION OF THE SERBIAN MEDICAL SOCIETY WITHIN THE EPIDEMIC COVID 19 IN THE REPUBLIC OF SERBIA (Engrami, 2021)
Psychomotor agitation (PMA) or psychomotor restlessness is a condition characterized by anxiety, excitement, impaired behavioral control, accelerated motor skills, superficial verbal contact, and a tendency to react impulsively. In practice, the most important thing is to detect episodes of psychomotor agitation in their earliest manifestation in order to avoid complicating symptoms and prevent numerous health, legal and economic consequences that untimely recognition brings. Psychomotor agitation and delirium can be one of the symptoms of COVID 19 infection. In this context (interactions with antiviral and antimalarial th used in the treatment of covid infection and complications of the viral infection itself) we consider agitation therapy as a condition that requires urgent treatment.
Keywords: covid19; agitation; therapy